EmQuestão Vol. 19, n. 2 (2013) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
EmQuestão Vol. 19, n. 2 (2013)Link de acesso ao númerohttp://www.seer.ufrgs.br/index.php/EmQuestao/issue/view/2260/showToc